THE MORPHOLOGICAL AND MORPHOMETRIC STATE OF THE LIVER’S VASCULAR-TISSUE STRUCTURES IN THE OFFSPRING OF INTACT EXPERIMENTAL RATS DURING POSTNATAL ONTOGENY DYNAMICS (experimental study) - Maloxat B. Nazarova; Dilorom B. Adilbekova; Abdulaziz A. Akhrorov; Sardorjon S. Toshpulatov; Farangiz O. Rustamova (Central Asian Journal of Medicine, 2025)
Our research has shown that the morphological examination of the liver’s vascular-tissue structures in rat offspring during the early postnatal periods indicates that the processes of organ development and formation are not yet fully completed by the time of birth. During the early postnatal period, in connection with functional formation, not only does the size of the organ increase, but the processes of structural reorganization also occur. According to our data, the processes of development and formation of the liver’s structural composition in rats are completed by the 30th day of postnatal development.